Sedimentary Environment and Enrichment of Organic Matter During the Deposition of Qiongzhusi Formation in the Upslope Areas—A Case Study of W207 Well in the Weiyuan Area, Sichuan Basin, China - Zhao, Lei; Liu, Shugen; Li, Guoqin; Zhang, Menglin; Liang, Xiao; Li, Junxiang; Xu, Jianliang (Frontiers in Earth Science, 2022)
For a more in-depth analysis on the marine chemical condition during the earliest Cambrian, mechanism of organic matter enrichment and exploration potential of shale gas resources, based on the petrology, organic geochemistry, and elemental characteristics of the W207 Well, this study discuss the Early Cambrian paleo-ocean environment and factors controlling of organic matter enrichment during the deposition of black strata Qiongzhusi Formation (Fm) in the upslope areas, southwestern Sichuan Basin, Yangtze Block, China. The sedimentary cycles show that during the depositon of fine-grained Qiongzhusi Fm, interactive cycles of multiple deep-water and shallow-water shelf developed, and were controlled by the rise and fall in sea level. In particular, the slope turbidite (fan) and gravity flow sediments indicate that the shallow-water shelf facies were dominant in the upslope area (SW Sichuan Basin) were not in deep water for a long time, and the sedimentary thickness of the organic rich black shale was limited. Evidence from organic geochemistry indicates that the organic matter of the Qiongzhusi Fm from the W207 Well was mainly of type I kerogen, with a high degree of thermal evolution, little residual hydrocarbon, and low capacity for hydrocarbon generation. The redox parameters indicate that the marine environment on the upslope was medium restrictive, with some upwelling. The seawater had undergone a transformation according to anoxic–oxidic. Therefore, paleo-ocean productivity in the upslope area was generally low, and exhibited a prominent downward trend from bottom to top. Given its high risk of exploration, the authors suggest that the direction of shale gas resource evaluation should change to the intracratonic sag (downslope) area, which is characterized by deep-water shelf facies.